New Optimal AH Method for Solving Transportation Problems - Kalhoro, Huzoor Bux; Soomro, Abdul Sattar; Ahmed, Reem Mahmoud; Shaikh, Kashif (International Journal of Supply Chain and Logistics, 2025)
The main purpose of the paper is to develop a direct, new optimal method to minimize the total transportation cost from origin to destination by meeting supply and demand limits. Hundreds of transportation problems from different research papers have been solved by a new proposed optimal method. Its results are compared with the well-known and established techniques, especially the Steeping Stone method (1954) and the Modified distribution (MODI) method (1989), and it is found that all results obtained by the proposed method are optimal. In this paper, we have proposed a new optimal method, called the AH method for solving transportation problems. In the proposed method, there is no need to find an initial basic feasible solution (IBFS) because this is a direct method to find the optimal solution. Whenever the Steeping Stone method and the MODI method depend upon an initial feasible solution because both are not direct methods. A software package based on Java script programming designed by Html, CSS and Bootstrap was developed for new optimal AH method. Hundreds of balanced and unbalanced problems of different sizes solved from different research papers by using the software that provided optimal results.